The Influence of Technology Use, Education Level, Labor Force, Investment, and Exports on Economic Growth in Indonesia - Egi Nabila; Ansofino; Nilmadesri Rosya (Global Action and Education for Society, 2026)
This study aims to analyze the influence of technology utilization, education level, labor force, investment, and exports on economic growth in Indonesia during the period 2000–2024. This research employs a quantitative approach using secondary data obtained from the Central Bureau of Statistics (BPS), the Ministry of Communication and Information Technology, and the World Bank. Data analysis was conducted using multiple linear regression with the EViews program. The results indicate that, partially, technology utilization, education level, labor force, investment, and exports do not have a significant effect on Indonesia’s economic growth. Similarly, simultaneously, these five variables also show no significant impact on economic growth. These findings suggest that such fundamental factors require stronger structural policy support and quality improvements in their implementation to make a tangible contribution to national economic growth.